Structure, composition and plant diversity in tropical forests of Osa Biological Corridor, Costa Rica - Morales-Salazar, Manuel Safrirh (2013)
Were established 14 permanent plots (50 m x 100 m) distributed in different forests of the Osa Biological Corridor (CBO), Costa Rica. We evaluated the floristic composition, species of high conservation value, ecological guild composition and vertical structure in four successional stages of forest ages: 5 to 15 years, 15 to 30 years, more than 30 years and primary. All trees with d ≥ 5 cm were botanically identified; their diameter (d), total height and ecological group were determined. The results indicated that secondary forests have great potential for conservation and connectivity of areas with high ecological value, safeguard and develop as specimens of primary forests, endemic and threatened to some degree. Primary forests differ in terms of the secondary species abundance shade – tolerant and palms. Forests within the same geographical area or closer together were more similar floristically. It was found that primary forests north of the CBO, differ from those in the south, and secondary forests differ in terms of species abundance shade – tolerant and palms. The  increase in the maximum height of the trees, the increasing number and basal area of shade-tolerant species as a function of age, and the percentage of floristic affinity of the vertical strata secondary forests compared to primary, mainly on the lower floor, said that secondary forests are recovering well, with a tendency to resemble the primary forests. However, they will take many years to possess the composition and structure of forests.